The Influence of Persistence on Job-Change Intentions among Industrial Millennial Workers - Deden Sutisna; Rima Rahmayanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
It is challenging to envision a situation where the level of grit among industrial company workers remains unidentified and unmeasured especially considering that these individuals belong to the millennial generation, which is widely regarded as difficult to manage. Moreover, it remains unclear whether grit influences job-hopping behavior or vice versa. In this sector, job-hopping appears to be both a reflection and a determinant of worker grit. A strong association exists between employee grit and job-hopping, which in turn is linked to improvements in management outcomes. This study employed a quantitative method, distributing 100 questionnaires among a population of 328,673 workers in the industrial sector located in Purwakarta Regency, West Java, Indonesia. The findings suggest that higher grit levels among workers contribute to increased job-hopping behavior, and there is a significant correlation between grit and positive developments in job-hopping patterns. It is recommended that company management adopt a persuasive policy approach to strategically manage worker grit, ensuring that job-hopping remains under control. One of the biggest challenges for management is to handle the constantly shifting work behavior of millennial employees an inconsistency that is likely to persist due to the unique characteristics of this generation in the workplace.